The Land, the Story Teller and the Great Cauldron of Making (Fourth World Journal, 2010)
In a mystical land where storytellers hold a revered position, Zaddik emerges as a new storyteller with exceptional abilities. However, when darkness envelops the land, Zaddik faces challenges in combating the evil disguised as holiness, leading to a loss of power in his stories. Through a journey of grief and self-discovery, Zaddik learns to embrace nothingness and reconstruct meaning through his own narrative. In a separate narrative, Zaddik's act of hurling bones into a cauldron unleashes a great light that brings redemption and joy to the land and its inhabitants, captivating even the gods. Patricia Spence, the author, shares insights from her work with indigenous communities, focusing on themes of soul loss and colonization. The articles highlight the significance of storytelling in preserving societal harmony and restoring meaning in the face of darkness.